(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Laboratory experiments were carried out to determine the effects of harvesting stages on the seed quality of chickpea. Chickpea seed of three varieties (BARI Chola-5, BARI Chola-6 and BARI Chola-8) were collected at three harvestings times i.e. from three different times at 7 days interval prior to harvesting, viz. i) when the pods were yellowish with a few yellow greens (H1 stage), ii) when most of the pods were light brown with a few yellow (H2 stage), and iii) when all the pods were completely brown and dry (H3 stage). Significant variation was observed in three varieties of chickpea for all the parameters studied except vigour-I. The highest germination percentage, root length, shoot length, root plus shoot length and vigour-II was observed in BARI Chola-5 which was significantly higher over BARI Chola-8. Dry weight was found to be significantly higher in BARI Chola-8 which was identical to BARI Chola-6. Moisture content was significantly higher in BARI Chola-8. Seed collected at the stage when most of the pods were light brown with a few yellow (H2 stage) recorded the highest germination percentage, dry weight, vigour-I and root length. Pods (H1 stage) gave the highest moisture content in seeds. BARI Chola-5 seeds recorded the highest germination at H2 stage. Interaction effects of varieties and harvesting stage had non-significant effect on germination percentage, vigour-I, shoot length and vigour-II in both the years. Keywords: Chickpea, Harvesting stage, Storage, Vigour, Moisture, Germination DOI: 10.3329/bjsir.v44i3.4403 Bangladesh J. Sci. Ind. Res. 44(3),303-310, 2009